PTU-053 Dysplasia diagnosis at barrett's surveillance – seattle protocol dominant strategy in real world non-expert centres. Issue 2 (June 2019) - Keyte, Georgina; Iqbak, Muhammad; Viswanath, YKS; Dhar, Anjan
Abstract : Introduction: Detection of dysplasia at Barrett's surveillance depends on a number of factors - the endoscopist's skill, use of advanced imaging, adherence to Seattle protocol, and high risk patient factors like male sex, smoking, length of Barrett's segment and family history of oesophageal adenocarcinoma. Whether the high rates of dysplasia diagnosis reported from expert tertiary centres can be replicated in the real world is debatable. Aim: The aim of this study was to analyse the routes to dysplasia diagnosis in a dedicated Barrett's surveillance programme in County Durham, specifically looking at the grade of the endoscopist, use of advanced imaging (NBI, Acetic Acid), diagnosis by targetted biopsy vs. Seattle Protocol, and the nature of dysplasia (Low grade vs. high grade). Methods: An electronic database search of over 600 Barrett's surveillance histology was carried out for the period 2015–2018, extracting all reported dysplasia. The endoscopy database was then interrogated for the following: patient demographics, grade of endoscopist (medical consultant gastroenterologist, non-medical endoscopist and surgical consultant), sedated vs. unsedated procedure, visible dysplasia, HD-white light vs. image enhancement, length of Barrett's segment and Prague classification, Paris classification of any visible lesions, targeted vs. Seattle Protocol biopsies, and grade of dysplasia. All endoscopies were carried out using high-resolution scopes and where a visible lesion was identified a targeted biopsy was taken. Results: 94 patients with dysplasia were analysed, M:F ratio 3.5:1, mean age 71 yrs. Barrett's length ranged from 1–14 cm, with 32% endoscopists reporting the Prague classification. Surveillance was done by: consultant gastroenterologists (48pts), nurse endoscopists (42pts) and consultant surgeons(4pts). Although only 3.2% endoscopists explicitly mentioned a Seattle biopsy protocol in their report, histology showed that protocol had been followed in 51% of endoscopies. 52% consultant gastroenterologists, 45% nurse endoscopists and 100% consultant surgeons adhered to Seattle biopsy protocol. The distribution of low grade dysplasia (LGD):high grade dysplasia (HGD):carcinoma- in-situ (situ) in the Seattle group 21:21:6 compared with a random biopsy protocol of 8:19:19. Image enhancing techniques were used in just 4% pts. Conclusions: In this real world NHS study, we found that after 4 years of the BSG guidelines, visible dysplasia is extremely difficult to detect. The Seattle biopsy protocol was followed in only 51% of endoscopies. There is a need for quality improvement & training for Barrett's surveillance amongst medical and non-medical endoscopists, including image enhanced surveillance and chromoendoscopy.